PENGARUH PENGGUNAAN BAHAN BAKAR ALTERNATIF TERHADAP EMISI VOC (VOLATILE ORGANIC COMPOUNDS) DAN PERSEBARANNYA DI INDUSTRI SEMEN (PT.X) - Ancilla A, Louisa
To reduce the use of fossil fuels, cement industries in Indonesia began using alternative fuels among which were solid waste and rice husk. Along with the application, the output is visible in the measurement of cement industry began to show volatile organic compounds emissions. This study was conducted to determine whether the source of VOC emissions come from alternative fuels that have been used in the cement industry by using theoretical calculations and statistical analysis. Beside that the simulation of VOC emission dispersion is performed specifically for benzene, toluene, ethylbenzene and xylene (BTEX) to determine the pattern of distribution pollutant around the plant. Based on theoretical calculation, although in a very small quantitites but solid waste and rice husk are known produce VOC emission. For the result of statistical analysis, showed the weak strength of relationship between alternative fuels and VOC emission produced. AERMOD dispersion simulations performed using the measurement time of 3 hours and 8 hours. Pollutant dispersion simulations showed the highest concentrations of pollutants in maximum emission rate in 2011 at 3 hours measurement are benzene 2,927 ?g/m3, toluene 0,303 ?g/m3, ethylbenzene 0,025 ?g/m3, and xylene 0,079 ?g/m3. At 8 hours measurement showed the highest concentration in maximum emission rate are benzene 2,168 ?g/m3, toluene 0,234 ?g/m3, ethylbenzene 0,019 ?g/m3, and xylene 0,061?g/m3. Then the values obtained were compared with ambient air quality standard to international regulation which is OSHA. It is known that the value of the result emission rate were still below the quality standard.